A Comparitive Study on Efficacy and Safety of Vildagliptin-Metformin versus Glimepiride - Metformin in Type 2 Diabetes Mellitus Patients - Prathap Bingi; Shaik Kareemulla; B. Himabindu; Khan, D. Sheklane; Ramu, G.; Rafi, S. Mahammed (Indian Journal of Pharmacy & Drug Studies, 2023)
Background: Inadequate control of blood glucose in patients leads to micro or macrovascular complications. Metformin is an initial drug used to treat diabetes. In case of inefficient glucose control with Metformin, add-on therapy is recommended. The motto of our study is to compare the efficacy and safety of Vildagliptin-Metformin with Glimepiride – Metformin in type 2 diabetes. Aim & Objectives: This study was aimed to compare the efficacy and safety of Vildagliptin-Metformin with Glimepiride Metformin for patients with type 2 diabetes mellitus at Government General Hospital (GGH-RIMS), Kadapa. Objective: To assess the prognosis report, and compare the effectiveness and safety profiles of Group I (Vildagliptin Metformin) patients with Group II (Glimepiride-Metformin) patients and counsel them about a multi-disciplinary treatment approach by providing patient information leaflets to exhibit a better life. Methodology: A single-center prospective observational study was conducted for 6 months in the general medicine department at a government general hospital, in India. A total of 100 patients were recruited for this study and divided into 2 groups of 50 patients each. Vildagliptin-Metformin group 1 and Glimepiride-Metformin group 2. Results: Glycated hemoglobin (HbA1C), fasting blood sugar levels (FBS), and random blood sugar levels (RBS) parameters are taken as primary and secondary endpoints to compare groups as per efficacy. In terms of safety weight gain, hypoglycemia, and other gastrointestinal adverse effects are considered. The difference between values of baseline and final follow up of HbA1C, FBS, RBS is 0.50%, 20mg/dl, 85mg/dl in group 1 (V-M); whereas 0.35%, 15mg/dl, 55mg/dl in group 2 (GM) respectively. 24 ADRs with respect to hypoglycemia, weight gain, abdominal pain, muscle tenderness, and diarrhea are observed in group 1 (VM) group and 46 ADRs are observed in group 2 (G-M). Conclusion: Vildagliptin-metformin treatment provided favorable glucose control comparable to that of glimepiride-metformin treatment. It also resulted in better adverse event profiles with lower risks of hypoglycemia and weight gain.